STRATEGI SELF-MANAGEMENT UNTUK MENGEMBANGKAN STABILITAS EMOSI SISWA - Annisa Ul Azmi; R.Ika Mustika; Ecep Supriatna (IKIP Siliwangi, 2021)
Self-management is a set of techniques for changing behavior, thoughts, and feelings. Self-management can control emotions and control negative emotions and express emotions in the right way without overdoing it. The purpose of this study was to determine the extent of counseling services with self-management strategies to develop the emotional stability of class X students. The approach used in this study was a qualitative approach with a descriptive type of research. This research is a case study of one student who has problems in regulating his emotional stability. The results showed that self-management strategies can improve students' emotional stability, seen from the way students manage emotions after being given counseling techniques. Students are able to rearrange the environment as an antecedent to certain responses, as well as present themselves and determine their own positive stimulus that follows the desired response. Keywords: : counselling, self management, emotional stability